Financialization and Level of Happiness in the Context of Sustainable Development. The Case of Central and Eastern European Countries - Ostrowska, Aleksandra; Włodarczyk, Bogdan (Journal of Finance and Financial Law, 2024)
The purpose of the article. The article aims to identify and assess the impact of the financialization process on the level of happiness as an effect of sustainable development in selected Central and Eastern European countries in 2012–2022.Methodology. The research used panel models. The World Happiness Index (WHI) was adopted as the dependent variable, taking into account social aspects of sustainable development. Financialization measures included the Financial Development Index (FDI) published by the International Monetary Fund and credit to the private sector (as a % of GDP). The models were estimated using OLS, fixed-effects and random-effects estimators. Macroeconomic variables were included in the set of explanatory variables. The most effective estimator was selected using Wald, Breusch-Pagan and Hausman tests. Robust standard errors were imposed on the models.Results of the research. In the estimated models, the significance of parameters in the case of financialization varied depending on the estimator used. The Financial Development Index was an insignificant variable in all models. Clear significance was observed in relation to credit to the private sector (as % of GDP). Regardless of the financialization measure adopted and the estimator used, the obtained parameters for financialization indicators were negative. Although financialization may be an instrument for financing sustainable development, it does not have a positive impact on the level of happiness that results from it. The basic reasons may lie in the too low scale of financing activities related to sustainable development or in the inadequate structure of this financing. Changes in financing are needed and its redirection to activities aimed at achieving sustainable development and happiness. Future research should use other measures of financiakization and happiness that take into account aspects of sustainable development and include other countries to make a comparison.